Review on Nanosponge - A Contemporary Drug Delivery Approach - Senthil Venkatachalam (Journal of Global Pharma Technology, 2019)
An effective operational method of targeted drug delivery system has been an aim for the researchers in the pharmaceutical field for a prolonged time, but it has been mostly discouraged due to the complex chemistry behind in it and the difficulty in designing such a system, Nano sponges are such a delivery method using which targeted delivery to a specific site is possible and extensive researches are being done on nanosponges due to their such activity. Nanosponges as the name suggests are minute sponge like structures with size as small as a virus in which drugs can be incorporated into the voids. Studies have shown that these kind of formulations tends to circulate in the body until the targeted site is reached for the release and further it sticks at the site and releases the drug, since it can be modified to deliver the drug site specifically and hence can be more effective than other methods of delivery, another factor for consideration of nanosponges in targeted delivery is due to their good aqueous solubility which can be used to deliver drugs which are poorly solubleKeywords: Nanosponge, Cyclodextrin, Cross Linking, Functionalized Nanosponges.